2011
DOI: 10.1016/j.scitotenv.2011.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of lead and arsenic in traditional Indian medicines

Abstract: Arsenic and lead have been found in a number of traditional Ayurvedic medicines, and the practice of Rasa Shastra (combining herbs with metals, minerals and gems), or plant ingredients that contain these elements, may be possible sources. To obtain an estimate of arsenic and lead solubility in the human gastrointestinal tract, bioaccessibility of the two elements was measured in 42 medicines, using a physiologically-based extraction test. The test consisted of a gastric phase at pH 1.8 containing organic acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 36 publications
1
40
0
4
Order By: Relevance
“…The SBF test conditions were set up to be as close to the in vivo situation as possible to simulate the gastric and intestinal digestion process. The solid:liquid ratio was set to 1:100 and the two-stage extraction process was similar to that used by others (Cabanero et al, 2004;Koch et al, 2011) with slight modification (Fig. 1).…”
Section: Sample Collection and Pretreatmentmentioning
confidence: 99%
“…The SBF test conditions were set up to be as close to the in vivo situation as possible to simulate the gastric and intestinal digestion process. The solid:liquid ratio was set to 1:100 and the two-stage extraction process was similar to that used by others (Cabanero et al, 2004;Koch et al, 2011) with slight modification (Fig. 1).…”
Section: Sample Collection and Pretreatmentmentioning
confidence: 99%
“…The deliberate addition of minerals, metals and metalloids to an herbal remedy is known as rasa shastra, and previous studies have shown that remedies prepared in this way can contain highly elevated concentrations of toxic metals like lead and mercury, as well as the toxic metalloid, arsenic (Saper et al, 2004(Saper et al, , 2008. Elevated concentrations can also be present in remedies not classified as rasa shastra, presumably from metals and metalloids introduced in plant material or incidentally during manufacturing (Saper et al, 2008;Koch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Risk has been estimated for the use of several remedies according to dosing regimes indicated by the manufacturers of the medicines for mercury, lead and arsenic (Saper et al, 2004(Saper et al, , 2008Koch et al, 2011). For arsenic and lead risk calculations, the incorporation of solubility information, specifically bioaccessibility, decreased the number of medicines that exceeded acceptable daily intakes (Koch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar kind of study done by Koch I et al, bioaccessible lead was found in in 72% of the 42 samples of traditional Indian medicines 7 .…”
Section: Resultsmentioning
confidence: 53%